Cable Test and Breakdown Voltage Determination of Joysense Cable Insulation - Muhammad bin Yahya; Muhammad Nazrolni Azmi bin Izani (Institute of Advanced Engineering and Science, 2017)
Cross-linked Polyethylene (XLPE) has been used as the insulation for polymeric power cables for its superior advantages. This type of cable insulation are famously known and used for their good dielectric properties, mechanical properties, thermal properties, and probability to be utilized at high temperature. This study is of four (4) parts; designing suitable method for cable test, accelerated testing procedures applied to XLPE insulation for high voltage cables, online partial discharge determination, and aging test. To study the insulation durability to AC high voltage operation, the breakdown strength and aging were investigated under different setting of temperature. The breakdown voltages of XLPE were measured at different temperatures of 300C, 500C and finally at 700C. Lastly, the aging effect of cable insulation was observed by conducting the AC breakdown voltage test after the aging process. Results showed that the breakdown voltage and aging of XLPE cables will decrease with increase of temperature setting.